Size matters: a review of the challenges in and importance of multimodal approaches to the management of patients with small, node-negative, triple-negative breast cancer - Prasath, Vishnu; To, Briana; Quiroga, Dionisia M.; Oppong, Bridget A.; Johnson, Kai; Facer, Benjin; Wesolowski, Robert (Frontiers in Oncology, 2025)
Patients diagnosed with small (T1a-c) node-negative triple-negative breast cancer (TNBC) comprise an understudied population. These patients have been commonly excluded from participation in large, practice-changing clinical trials that establish improvements in disease-free and overall survival due to neoadjuvant or adjuvant systemic therapies as well as innovative local therapies. Despite this, patients with small, node-negative TNBC are at higher risk for early relapse compared to patients with hormone receptor-positive breast cancer matched for the same T and N stage. We highlight retrospective and prospective studies that analyze the benefit of chemotherapy in small node-negative TNBC patients. Furthermore, we discuss current guidelines for radiation therapy, surgical management, and relevant studies examining local therapy for patients with early-stage node-negative TNBC.